2009
DOI: 10.1089/gtmb.2009.0096
|View full text |Cite
|
Sign up to set email alerts
|

IMPDH2Genetic Polymorphism: A Promoter Single-Nucleotide Polymorphism Disrupts a Cyclic Adenosine Monophosphate Responsive Element

Abstract: Inosine 5'-monophosphate dehydrogenase (IMPDH), which catalyzes a key step in the de novo biosynthesis of guanine nucleotide, is mediated by two highly conserved isoforms, IMPDH1 and IMPDH2. In this study, IMPDH2 genetic polymorphism was investigated in 96 individuals of Caucasian origin. Four single-nucleotide polymorphisms were identified, comprising one previously described single base-pair substitution in the close vicinity of the consensus donor splice site of intron 7 (IVS7+10T>C), and three novel polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For example, a T-to-G substitution in the promoter region of the human IMPDH2 gene, a homolog of E. coli purA encoding SAMP synthetase (Fig. 1), reduced gene expression by 50-60% (15). While the present studies focused on a complete loss of this gene, it is reasonable to assume that a 50-60% decrease in SAMP synthetase activity could cause measurable increases in hypoxanthine incorporation into DNA and RNA in human cells affected with the genetic polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a T-to-G substitution in the promoter region of the human IMPDH2 gene, a homolog of E. coli purA encoding SAMP synthetase (Fig. 1), reduced gene expression by 50-60% (15). While the present studies focused on a complete loss of this gene, it is reasonable to assume that a 50-60% decrease in SAMP synthetase activity could cause measurable increases in hypoxanthine incorporation into DNA and RNA in human cells affected with the genetic polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…These synergies suggest that even modest changes in the activities of pairs of these enzymes caused by genetic polymorphisms could result in increased misincorporation of hypoxanthine into nucleic acids in humans. Given the large reductions in activity caused by common genetic polymorphisms in the human homologs of purA and rdgB (15,16), a substantial number of humans could possess polymorphisms that affect two or more purine metabolism genes, with the consequence of increased incorporation of deaminated nucleotides into DNA and RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The null genotype and restrictive growth phenotype of cultured Δ impdh parasites authenticates a single IMPDH encoding locus in L. donovani . In contrast, mammalian cells have two similar but distinct IMPDH genes [15]. …”
mentioning
confidence: 99%
“…Our findings about the Hani minority were in accordance with the reports of Gu et al 24,30,96,97 However, our research about the Yi minority showed no association in -532T/C (rs5046), which was in accordance with the finding of Zhu et al 33 This inconsistency could be attributed to the different genetic backgrounds, living habits, and environmental factors among different populations. Since the previous studies revealed that the variants localized near the 5′ region of a gene might be associated with the regulation of this gene expression level, 100102 the functional effect of rs5046 polymorphism localized at the promoter region of AGT gene on the expression level of this gene was predicted by p -match. The result revealed that the sequence (TGTGTTTTCC) containing the C allele of rs5046 could be captured by the TF c-Rel, suggesting that the C→T single nucleotide substitution of rs5046 would change the sequence structure of the TF binding site, thereby affecting the binding affinity between this TF c-Rel and its binding site.…”
Section: Discussionmentioning
confidence: 99%